1978
DOI: 10.1063/1.862278
|View full text |Cite
|
Sign up to set email alerts
|

Whistler wave ducting caused by antenna actions

Abstract: Whistler waves launched from an antenna damp away for small incident power. With increasing power, undamped nondiverging waves (the ducted waves) are observed, together with a field-aligned density trough and electron heating. However, the density trough is found not only in the wave propagation regime (ω/ωc<1), but also in the wave evanescence regime (ω/ωc≳1). This implies that the density depression is mainly created by the effect of the antenna near-zone field rather than by the wave radiation pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Stenzel's work in slowly-varying plasma was extended by Sugai and coworkers [Sugai et al, 1978a[Sugai et al, , 1978b[Sugai et al, , 1979[Sugai et al, , 1980. From the early 1980's laboratory research on whistler waves has continued but in directions that are not relevant to this discussion.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stenzel's work in slowly-varying plasma was extended by Sugai and coworkers [Sugai et al, 1978a[Sugai et al, , 1978b[Sugai et al, , 1979[Sugai et al, , 1980. From the early 1980's laboratory research on whistler waves has continued but in directions that are not relevant to this discussion.…”
Section: Introductionmentioning
confidence: 97%
“…As well, he goes on to measure the phase and amplitude distribution of the antenna radiation pattern in both uniform and slowly-varying plasmas. In the nonuniform case, refraction is observed as well as ducting in a density trough.Stenzel's work in slowly-varying plasma was extended by Sugai and coworkers [Sugai et al, 1978a[Sugai et al, , 1978b[Sugai et al, , 1979[Sugai et al, , 1980. From the early 1980's laboratory research on whistler waves has continued but in directions that are not relevant to this discussion.…”
mentioning
confidence: 97%
“…Density perturbations by ponderomotive force or thermal pressure can produce a density trough which guide whistlers [99][100][101]. Focusing resonance cones produces density holes, fast ions, and low-frequency turbulence [82].…”
Section: Nonlinear Whistlersmentioning
confidence: 99%
“…A number of important features of whistler wave radiation from monochromatic sources in the presence of density ducts have been documented in Refs. [10][11][12][13][14][15][16][17][18][19][20]. In particular, it has been demonstrated that under certain conditions, the presence of a duct can significantly improve the antenna coupling into whistler-mode waves.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of attention has particularly been devoted to whistler wave excitation in laboratory and space plasmas containing magnetic-fieldaligned density irregularities. [10][11][12][13][14][15][16][17][18][19][20][21][22] Such irregularities, commonly known as density ducts, can exist in the Earth's magnetosphere, in which they ensure guidance of whistler-mode waves naturally occurring under space plasma conditions. 25 Of no less interest are artificial density ducts that can arise due to various nonlinear effects near electromagnetic sources in laboratory and space plasmas.…”
Section: Introductionmentioning
confidence: 99%